Preparation and In-vitro characterization of ethylcellulose coated pectin alginate microspheres of 5-fluorouracil for colon targeting - Ramana G, Krishna Chaitanya A (Journal of Applied Pharmaceutical Science)
The main objective of the present study was to prepare and evaluate the colon-specific pectin alginate microspheres of 5-fluorouracil (5-FU) for the treatment of colon cancer. Calcium alginate beads were prepared by extruding 5-FU loaded alginate solution to calcium chloride solution and gelled spheres were formed instantaneously by ionotropic gelation reaction using different ratios of 5- FU and alginate, alginate and calcium chloride, stirring speeds (500-1500 rpm) and reaction time. The core beads were coated with ethyl cellulose to prevent drug release in the stomach and provide controlled dissolution of enteric coat in the small intestine and maximum drug release in the colon. Morphology and surface characteristics of the formulation were determined by scanning electron microscopy. In vitro drug release studies were performed in conditions simulating stomach to colon transit in the presence and absence of pectinase enzyme. No significant release was observed at acidic pH, however, when it reached the intestinal pH where ethyl cellulose starts to dissolve, drug release was observed. Also, release of drug was found to be higher in presence of pectinase enzyme. The DSC and FT-IR studies were also indicates there were no interactions between the drug and the polymers used.
Keywords: 5-FU, Pectin alginate beads, Ethyl cellulose, Scanning Electron Microscopy and Pectinase enzyme.